Late Holocene climatic changes in Tierra del Fuego based on multiproxy analyses of peat deposits - Mauquoy, Dmitri (2004)
A ca. 1400-yr record from a raised bog in Isla Grande, Tierra del Fuego, Argentina, registers climate fluctuations, including a Medieval Warm Period, although evidence for the 'Little Ice Age' is less clear. Changes in temperature and/or precipitation were inferred from plant macrofossils, pollen, fungal spores, testate amebae, and peat humification. The chronology was established using a 14C wiggle-matching technique that provides improved age control for at least part of the record compared to other sites. These new data are presented and compared with other lines of evidence from the Southern and Northern Hemispheres. A period of low local water tables occurred in the bog between A.D. 960-1020, which may correspond to the Medieval Warm Period date range of A.D. 950-1045 generated from Northern Hemisphere tree-ring data. A period of cooler and/or wetter conditions was detected between ca. A.D. 1030 and 1100 and a later period of cooler/wetter conditions estimated at ca. cal A.D. 1800-1930, which may correspond to a cooling episode inferred from Law Dome, Antarctica.